Near-Field Analysis and Design of Inductively-Coupled Wireless Power Transfer System in FEKO - Kim, Dowon; Sutinjo, Adrian; Abu-Siada, Ahmed (Applied Computational Electromagnetics Society, 2020)
Inductively-coupled wireless power transfer (WPT) system is broadly adopted for charging batteries of mobile devices and electric vehicles. The performance of the WPT system is sensitively dependent on the strength of electromagnetic coupling between the coils, compensating topologies, loads and airgap variation. This paper aims to present a comprehensive characteristic analysis for the design of the WPT system with a numerical simulation tool. The electromagnetic field solver FEKO is mainly used for studying high-frequency devices. However, the computational tool is also applicable for not only the analysis of the electromagnetic characteristic but also the identification of the electrical parameters in the WPT system operating in the nearfield. In this paper, the self and mutual inductance of the wireless transfer windings over the various airgaps were inferred from the simulated S-parameter. Then, the formation of the magnetic coupling and the distribution of the magnetic fields between the coils in the seriesparallel model were examined through the near-field analysis for recognizing the efficient performance of the WPT system. Lastly, it was clarified that the FEKO simulation results showed good agreement with the practical measurements. When the input voltage of 10 V was supplied into the transmitting unit of the prototype, the power of 5.31 W is delivered with the transferring efficiency of 97.79% in FEKO. The actual measurements indicated 95.68% transferring efficiency. The electrical parameters; 𝑉in , 𝑉out, 𝑍in , 𝜃, 𝐼in , and 𝐼out, had a fair agreement with the FEKO results, and they are under 8.4% of error.